2009
DOI: 10.1177/0899764009333050
|View full text |Cite
|
Sign up to set email alerts
|

On the Classical Meaning of Philanthrôpía

Abstract: The academic study of philanthropy presupposes a comprehensive definition that guides inquiry into what, exactly, philanthropy is and why it matters. At present, though, no such well-thought-out definition exists. Scholars tend to explore various facets of philanthropy, according to their particular academic interests, but without a comprehensive understanding of its full meaning. This article attempts to correct this lack of synoptic understanding by surveying prominent instances of usage and definitions of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…Agape qualifies other-worldly Christian mysticism towards a social ethics of this-worldliness in the same sense as does Weber’s (1985d) wahllose Nächstenliebe – unselective philanthropy. However, this is not to suggest that charitable acts are limited to Orthodox Christianity only, nor, for that matter, any Christianity (Sulek 2010). Examples of charity offered in literature embrace, for example, unmotivated gift and alms giving, personal sacrifice, mercy shown towards others, human creativity to continue God’s creation, and the substitution of the humble human stewardship of nature, people and organizations for arrogant ownership or domination (Genesis 22:1–19; Luke 10:33; Alfeyev 2009; Meyendorff 1983; Weber 1985d, 1988b).…”
Section: The Encompassing Orthodox Emotional Ethics Of Monastic Originsmentioning
confidence: 96%
See 1 more Smart Citation
“…Agape qualifies other-worldly Christian mysticism towards a social ethics of this-worldliness in the same sense as does Weber’s (1985d) wahllose Nächstenliebe – unselective philanthropy. However, this is not to suggest that charitable acts are limited to Orthodox Christianity only, nor, for that matter, any Christianity (Sulek 2010). Examples of charity offered in literature embrace, for example, unmotivated gift and alms giving, personal sacrifice, mercy shown towards others, human creativity to continue God’s creation, and the substitution of the humble human stewardship of nature, people and organizations for arrogant ownership or domination (Genesis 22:1–19; Luke 10:33; Alfeyev 2009; Meyendorff 1983; Weber 1985d, 1988b).…”
Section: The Encompassing Orthodox Emotional Ethics Of Monastic Originsmentioning
confidence: 96%
“…Weber’s conclusions on the contingent character of legal and economic rationalization led him to ethical considerations driven by his concern with impersonalized chilling of human relations in a world disenchanted by rationalization. One starting point (Sulek 2010) comprises classical antiquity’s stress upon philanthropia and caritas – charity. Christian ethics steps in with the parable of the Good Samaritan (Luke 10:25–37) with the core characteristic philosophers call supererogation – good deeds that remarkably exceed what duty demands (Heyd 2006).…”
Section: Towards Elaborating a Weberian Ideal-type Theorymentioning
confidence: 99%
“…Philanthropy conceptually has myriad of definitions and explanations from its ancient conceptualization to it modern meaning (Sulek, 2010a , b ). Ylvisaker ( 1987 ) categorized five foundations types in the United States including “company-sponsored foundations, independent foundations, operating foundations, community foundations and public foundations” (as cited in Jung et al, 2018 ), p. 897.…”
Section: Philanthropy and Philanthropic Foundationsmentioning
confidence: 99%
“…Conceptually, philanthropy’s exact meaning is often contested (Daly, 2012 ; Sulek, 2010a , b ). Expansively, philanthropy is the promotion of civil society, civic action, encouragement of volunteerism and the advancement of well-being (Sulek, 2010a , b ).…”
Section: Philanthropy and Philanthropic Foundationsmentioning
confidence: 99%
“…Philanthropy is a contested term (Daly 2012). Through his reading of texts, Sulek (2010a; 2010b) found that definitions evolved over the centuries from focusing on civilization, politics, nature, and love for mankind to more modern notions of advancing well-being, volunteerism, giving, and social relations. Based on Josiah Royce’s work, Goldfarb (2011) conceptualized philanthropy as loyalty.…”
Section: Definitionsmentioning
confidence: 99%